Isolation and identification of different candida species from urinary tract catheterized patients and its relation to IL-17 - Farhan , Mohammed Sami (American Journal of Biology and Natural Sciences, 2026)
Background: The capacity to formation biofilms by yeasts on the surfaces of medical devices, such as urinary catheters, is a significant factor in their potential to induce human disease. Recent studies has demonstrated that biofilms play essential roles in over 65% of microbial infections. Aim of the study: The present study aimed to identify various Candida spp isolated from the urine of catheterized patients and to examine their biofilm formation capability, as well as to evaluate the amount of IL-17 in these patients. Materials and methods: One hundred samples were obtained from patients with Catheter-associated urinary tract infections CAUTIs. The sample collecting technique includes both genders, males and females, of all ages and various disease cases from hospitalized patients at Tikrit Teaching Hospital. The samples were gathered from September 2024 to January 2025. Result: A total of 100 patients with CAUTIs, 67 (67%) were positive for candidia species which were alone or mixed. This study reveals that the isolated yeast species consist of 30% C. albicans, 25% C. parapsilosis, and 33% C. tropicalis. The test results indicated a substantial disparity in the quantity of isolates that generated biofilms compared to those that did not. Among 30 samples, 20 isolates of C. albicans exhibited biofilm formation, while C. tropicalis demonstrated biofilm formation in only 18 isolates. The isolate of C. parapsilosis also produced a biofilm, indicated by the emergence of a black colony. Conclusion: The present study showed increase IL-17 in patients with positive result of candidiasis from CAUTIs were(124±9.44) ng/ml and control(91.85±7.22), at p-value <0.05.